Molinism’s Value in Easing Mistrust of God Stemming From Suffering and Divine Silence - Breitenbach, Zachary (Perichoresis, 2021)
One issue that sometimes produces mistrust of God in the life of a Christian is God’s perceived silence when He allows a trial to enter the believer’s life—especially when the believer has been faithfully praying that God would not allow it and there is no evident reason why God would not answer this prayer. This paper examines the nature of trust and some key reasons why it is difficult to trust God. It then argues that accepting the truth of human libertarian freedom and divine middle knowledge provides a powerful basis for thinking that God has meticulous providential control over the world without implicating God in evil, and this can help believers to trust God when they face trials and wrestle with His silence and apparent unresponsiveness to prayer.